Determinant of Online Purchase Decision of UIN Mataram College Student Using Lazada Application: Trust as Intervening Variable - Donny Dharmawan; Bahtiar Efendi; Silvia Ekasari; Posman WH hasibuan; Aat Ruchiat Nugraha (Yayasan Riset dan Pengembangan Intelektual, 2023)
Nowadays, one option that helps customers purchase the things they need more easily is to shop through the marketplace. The issues of supply and demand are not the only ones that face the growth of internet commerce. More than that, though, a number of variables can affect how these days rapidly expanding internet businesses operate.This study aims to analyze and examine the influence of online customer review, celebrity endorser and price discount on online purchase decision of UIN Mataram College Student using Lazada Application with trust as an intervening variable. This study is causally associative with quantitative approach. The data was collected using questionnaires were distributed online to college student as Lazada application users via WhatsApp by filtering questions according to the characteristics of respondents. The type of sampling method used is non-probability sampling, namely purposive sampling. The number of samples in the present research was 60 respondents. The data analysis with Partial Least Squares-Structural Equation Modeling (PLS-SEM). The results of this study indicate that the online customer review, celebrity endorser, price discount and trust has a significant influence on online purchase decision of UIN Mataram College Student Using Lazada Application. The trust is proven to be able mediate the effect of prise discount on online purchase decision. While, trust is unable to mediate the influence of online customer review and celebrity endorser on online purchase decision of UIN Mataram College Student Using Lazada Application. The findings of this research can be reference for future researchers who will study similar problems.